2012
DOI: 10.1371/journal.pone.0038839
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Protects against Increases in Low Molecular Weight Hyaluronan and Inflammation in Asphyxiated Newborn Pigs Resuscitated with 100% Oxygen

Abstract: BackgroundNewborn resuscitation with 100% oxygen is associated with oxidative-nitrative stresses and inflammation. The mechanisms are unclear. Hyaluronan (HA) is fragmented to low molecular weight (LMW) by oxidative-nitrative stresses and can promote inflammation. We examined the effects of 100% oxygen resuscitation and treatment with the antioxidant, N-acetylcysteine (NAC), on lung 3-nitrotyrosine (3-NT), LMW HA, inflammation, TNFα and IL1ß in a newborn pig model of resuscitation.Methods & Principal FindingsN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 78 publications
1
23
0
Order By: Relevance
“…Interestingly, we now found a positive correlation between MPO, NAG, and ADA1 activities in the cerebral cortex. This finding supports that ADA, as MPO, NAG, is a marker of the inflammatory process [43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, we now found a positive correlation between MPO, NAG, and ADA1 activities in the cerebral cortex. This finding supports that ADA, as MPO, NAG, is a marker of the inflammatory process [43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we used an established pig model of perinatal hypoxia-reoxygenation to induce oxidative stress [7]. We investigated a potential protective effect of NACA on newborn piglets exposed to hypoxia and reoxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our group showed previously that NAC attenuated the increase of oxidative stress in a neonatal pig model and reduced the levels of IL-1β [7]. Moreover, several investigators have displayed the many similar antioxidative effects of NAC and NACA [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamins A, E and N-acetyl-cysteine failed to reduce the occurrence of BPD in preterm newborns (175,185), and intravenous GSH did not improve acute respiratory outcomes in preterm baboons (160). In contrast to previous observations (6), a recent study in the animal model of hyperoxic resuscitation after perinatal asphyxia suggested a potential role for N-acetylcysteine in lung protection, as it was proved to reduce lung and systemic levels of OS and inflammatory markers (111). Moreover, pentoxifillyne, a phosphodiesterase inhibitor with immunomodulatory and antifibrotic features, has been investigated in the animal model of hyperoxia, and it was proved to reduce lung edema and neutrophils influx, while it increased lung activity of SOD, CAT, and GPx (9), in agreement with previous reports of reduced inflammatory cytokines in tracheal aspirates (173) and lung protection against mechanical ventilation-induced injury (81,158).…”
Section: Melatonin and Other Antioxidantsmentioning
confidence: 97%